The Prevalence, Predictors, and Health Consequences of Disagreement in Reports of Child Maltreatment Exposure. - Dunn, Erin C.; Ernst, Samantha C.; Nishimi, Kristen; Choi, Kristen R. (Child Psychiatry & Human Development, 2026)
The purpose of this study was to examine the prevalence, predictors, and consequences of disagreement between prospective caregiver and retrospective child reports of childhood physical and emotional maltreatment. The design was a secondary analysis of data from the Avon Longitudinal Study of Parents and Children, a three-decade long UK-based birth cohort. Prospective caregiver reports were in poor to fair agreement with retrospective child reports for physical and emotional maltreatment exposure, with caregivers tending to underreport exposure. Disagreement between reporters was associated with increased risk of depressive symptoms and substance use severity, but decreased risk for mental health diagnoses. Screening measures of childhood maltreatment exposure should take caution against using measures from different reporters interchangeably (i.e., from mother versus child). Disagreement in reports may indicate unmet need for mental health evaluation.